Building Defect: A Case Study at Universiti Tun Hussein Onn Malaysia - Sasitharan Nagapan,; Nurul Farahanis Mizlan, (Journal of Structural Monitoring and Built Environment, 2024)
Defects can have a significant impact on construction performance. A defect is not usually an outcome of a single cause, but rather occurs when multiple interrelated causes combine, forming a defect’s pathway. The safety, comfort, convenience, and health of building inhabitants are affected by any component, part, or section of a structure that fails. The goal of this study is to look into the defects that occurred at the FKAAB building in Universiti Tun Hussein Onn Malaysia (UTHM), Parit Raja. Employing a hybrid methodology involving visual inspection and a comprehensive questionnaire, this study endeavours to shed light on the building defects that occurred at the FKAAB building in. The visual inspection has been done to identify the type of defects that occurred in FKAAB building. The questionnaire also has been distributed to FKAAB building users. Therefore, questionnaire survey was carried out to obtain data from 374 respondents. The data obtained were analysed using mean, standard deviation and frequency by Statistical Package Social Sciences (SPSS). As the result of this study, preventive maintenance was chosen by the FKAAB building users as suggestion on how to improve the current practices of maintenance management at FKAAB building. As from the questionnaire, there is no critical defects occurred in FKAAB building. The overall comfortless for in the building area based on FKAAB building users perspective are in good conditions, which are the same results for the visual inspection. This study proposes potential for maintenance strategy to overcome the defects at FKAAB building.